О статусе некоторых хищнецов (Heteroptera, Reduviidae) палеарктической фауны - Пучков, П.В. (Вестник зоологии, 1987)
Pasira mediterranea D i s p o n s, 1959, stat. n.; Rhyncoris rubrogularis Horvath, 1879 and Coranus griseus (Rossi, 1790) are distinct species; Reduvius testaceus (H.— S. 1845) =R. verniciosus Miller, 1955, syn. n.; Rhynocoris annulatus (L., 1758)=Rh. annulatus hilaris D i s p o n s, 1968, syn, n. = Rh. annulatus vasconicus D i s p o n s, 1968, syn. n. = Rh. annulatus wastinensis D i s p o n s, 1968, syn. n.; Coranus aegyptius (F., 1775) sensu Wagner, 1952 = C. linnavuorii D i s p o n s, 1963, syn. n. = ? C. arenaceus Walker, 1870, syn. n.; Coranus griseus (Rossi, 1790) =Harpactor murinus R a m b u r, 1842 = Coranus persicus Wagner, 1952, syn. n. = C. aegyptius auct. pro Europa; Coranus angulatus S t a l, 1874 = C. pirzadae Miller, 1950, syn. n.; Coranus blandus J a k., 1904 = C. sahlbergi Wagner, 195a, syn. n; the finds of Pasira basiptera S t a l, 1859 in the Ukraine should be referred to P. mediterranea D s p., those of Rhynocoris cuspidatus R i b a u t, 1921 in Greece, Albania, Bulgaria — to Rh. punctiventris H.— S., and in Cyprus to Rh. iracundus Poda; Coranus griseus (Rossi) inhabits Europe (all European finds of C. aegyptius F. should be referred to this species), North-West Africa, Anterior and Middle Asia, C. aegyptius F. sensu Wagner inhabits arid zone of North Africa, Arabian peninsula, Iran, Afghanistan and extreme South of Uzbekistan (Termez).